The CEAC-Q for endurance athletes in competition, verification of a useful and time-efficient instrument for knowledge evaluation - Kosta, Orkida; Kosta, Ortensia (Edelweiss Applied Science and Technology, 2025)
Despite strong evidence that increased carbohydrate (CHO) availability promotes endurance performance, athletes frequently report eating less CHO during competition. The absence of practical or time-efficient methods for assessing athletes' understanding of CHO may be a contributing factor to these findings. Therefore, we attempted to validate a novel questionnaire to immediately assess endurance athletes' awareness of competition CHO guidelines. The students completed three subsections of the questionnaire (CHO metabolism, CHO loading, and pre-event meal), with each subsection valued at 15 points. The CEAC-Q was completed by 100 individuals, 56 of whom were women and 44 were men. The total CEAC-Q scores did not differ among the subsections regarding population-level averages for low (0–39%), moderate (39–69%), and high (70–100%) knowledge (p < 0.001). The CEAC-Q provides practitioners with a valid and effective psychometric tool for assessing athletes' comprehension of CHO competition standards. This evaluation not only helps to identify knowledge gaps but also offers suggestions for future dietary interventions aimed at improving athletic performance.